Ma che vita è questa? L’embrione è vita umana? - Vari, Autori (Il sogno della farfalla, 2006)
Supporting women’s right to interrupt a pregnancy or to assisted fecundation without first having clearly established that an embryo is not life, let alone human life, will not free women from the senseof guilt that they may be committing murder. The embryo and the foetus are only biological realities. At the 24th week the foetus then acquires the possibility of life that can be related to the term “vitality” which denotes a particular reaction of the retina to the light peculiar to human beings at birth. This transformation of human biological reality at birth generates human thought and overcomes the splitting inherent in religion between spirit and matter, mind and body. Therefore women can be free only when they are able to save their identity, in spite of the church and the dominion of reason. These are the themes discussed by scientists and politicians at a meeting organized by the Roman leftwing association at the Casa delle culture di Roma, which saw Massimo Fagioli making a significant contribution to the debate.